2013
DOI: 10.3117/plantroot.7.33
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of ericoid mycorrhizal fungi and root pathogens in Rhododendron: <I>In vitro</I> tests with plantlets in sterile liquid culture

Abstract: Plant protection against soil-borne diseases has been a challenge in horticultural production of Ericaceae for a long time. We tested the hypothesis that ericoid mycorrhizal fungi (ERMF) control root pathogens. Isolates of ERMF previously obtained from Calluna vulgaris and Rhododendron hirsutum were selected based on growth inhibiting activity against Oomycetes in dual agar plate tests. In addition, we assessed their impact on economically important Pythium spec. and Phytophthora cinnamomi in sterile Rhododend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Our results showed that human disturbances, especially the C. lanceolata plantation significantly changed community structure of root associated fungi of V. carlesii. The number of total and specific OTUs in PLF was much higher than those in two secondary forests with more DSE and pathogen species, and both of these fungal types were found often present in earlier stages of succession 27 68 69 with less mycorrhizal fungi 30 . More proportion of ERM fungi co-existed in the fungal communities in OGF probably due to the colonization rate of mycorrhizal fungi would increase along with the soil development years 21 70 .…”
Section: Discussionmentioning
confidence: 85%
“…Our results showed that human disturbances, especially the C. lanceolata plantation significantly changed community structure of root associated fungi of V. carlesii. The number of total and specific OTUs in PLF was much higher than those in two secondary forests with more DSE and pathogen species, and both of these fungal types were found often present in earlier stages of succession 27 68 69 with less mycorrhizal fungi 30 . More proportion of ERM fungi co-existed in the fungal communities in OGF probably due to the colonization rate of mycorrhizal fungi would increase along with the soil development years 21 70 .…”
Section: Discussionmentioning
confidence: 85%
“…Pisolithus tinctorius strain SMF, an ectomycorrhizal fungus, strongly inhibited the growth of V. dahliae [ 75 ]. Ericoid mycorrhizal fungi could protect the host plants from infections by pathogens such as Phytophthora cinnamomi and Pythium when they were sufficiently present in or on the roots [ 76 ]. Hage-Ahmed et al demonstrated that a direct antibiotic activity of root exudates from tomatoes towards F. oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…Lecanicillium (Zare and Gams 2001;Cho et al 2003;Heitman et al 2010;Pathrose et al 2014). The much pathogenic indicators in PLF may be due to the relatively lower ERM colonization in PLF, since extensive ERM colonization could enhance pathogen resistance of plants (Grunewaldt-Stöcker et al 2013). We should also notice that these putative pathogens (i.e.…”
Section: R a F Tmentioning
confidence: 99%